A model of four hierarchical levels to train Chinese residents' teaching skills for "practice-based learning and improvement" competency. Issue 7 (4th November 2015) - Yang, Ying-Ying; Yang, Ling-Yu; Hsu, Hui-Chi; Huang, Chia-Chang; Huang, Chin-Chou; Kirby, Ralph; Cheng, Hao Min; Chang, Ching-Chi; Chuang, Chiao-Lin; Liang, Jen-Feng; Lin, Chun-Chi; Lee, Wei-Shin; et al.
Abstract: Objectives: The current study focused on validating a protocol for training and auditing the resident's practice-based learning and improvement (PBLI) and quality improvement (QI) competencies for primary care. Methods: Twelve second-year (R2 ), 12 first-year (R1 ) and 12 postgraduate year-1 residents were enrolled into group A, B and C, respectively, as trainees. After three training protocols had been completed, a writing test, self-assessed questionnaire and mini-OSTE and end-of-rotation assessment were used in auditing the PBLI competency, performance and teaching ability of trainees. Results: Baseline expert-assessed PBLI and QI knowledge application tool writing scores were low for the R1 and R2 residents. After three training protocols, PBLI and QI proficiencies, performance and teaching abilities were improved to similar levels cross the three training levels of residents based on the expert-assessed writing test-audited assessments and on the faculty and standardized clerk-assessed end-of-rotation-/mini-OSTE-audited assessments. Conclusion: The different four-level hierarchical protocols used to teach group A, B and C were equally beneficial and fitted their needs; namely the different levels of the trainees. Specifically, each level was able to augment their PBLI and QI proficiency. This educational intervention helps medical institutions to train residents as PBLI instructors.